Prática de atividades físicas, doenças crônicas não transmissíveis e mortalidade entre adultos usuários da atenção primária do sistema público de saúde de Bauru, São Paulo: estudo longitudinal - Turi, Bruna Camilo [UNESP] (2015)
In the context of public health of low and middle-income countries, there are just a few longitudinal studies analyzing the effect of physical activity on health outcomes, especially among adults and / or elderly. Thus, the aim of this study was to verify the occurrence of noncommunicable diseases and mortality according to physical activity levels among adults aged >50 years, users of the Brazilian National Health System, during five years of follow-up. For this, 620 men and women from five Basic Healthcare Units of the city of Bauru / SP were followed from 2009 to 2014, and information on physical activity levels in different domains, occurrence of noncommunicable diseases, nutritional status, smoking habit, education and economic status were obtained. At the end of follow-up, it was found that the scores of occupational, leisure-time / transportation and overall physical activity decreased while scores related to sports practice / exercises increased from beginning to the middle, but fell at the end. The percentage of sufficiently active participants remained stable during the five-year follow-up. Regarding to noncommunicable diseases, it was found prevalence of hypertension of 80.2%, hypercholesterolemia 40.4%, diabetes 29.2% and 26.3% osteoporosis. Incidence of hypertension was 4.7%, 16.1% for hypercholesterolemia, diabetes mellitus 9.4% and 15.2% osteoporosis. Identifying risk factors for these four diseases, we found that hypertension remained associated with higher age, male sex and obesity. Hypercholesterolemia was associated only with obesity. Osteoporosis was associated to female sex and higher age. And diabetes remained associated with obesity and physical inactivity. Considering these findings, we evaluated the association between physical activity in different domains and incidence of type 2 diabetes, and it was found that individuals classified in the top quartile of physical activity during leisure-time in at least one ...